2014
DOI: 10.14283/jfa.2014.25
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Is Associated With Disability and Recent Hospitalization in Community-Dwelling Elderly: The Coyoacan Cohort

Abstract: Background: The phenotype of frailty proposed by Fried et al has shown to predict several adverse health-related outcomes in elderly populations worldwide; however, the description of such associations in Latin America is still scarce. Objective: To describe the association between frailty and recent hospitalization, disability for basic (ADL) and instrumental activities of daily living (IADL). Design, Setting and Participants:Cross-sectional study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…The authors’ research shows that the aging process of the patients decreased their functional ability to perform complex everyday life activities. Similar results were obtained in the studies of St John et al [ 28 ] and Su P. et al [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The authors’ research shows that the aging process of the patients decreased their functional ability to perform complex everyday life activities. Similar results were obtained in the studies of St John et al [ 28 ] and Su P. et al [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…This means that in patients with higher ADL and IADL scores, the severity of the frailty syndrome was less severe. In many other studies, conducted by Rivera-Almaraz et al [ 25 ], Papachristou et al [ 27 ], Avila-Funes et al [ 28 ], similar correlations were found between the frailty syndrome and performance scores on the ADL and IADL scales. In the study conducted by Avila-Funes et al, it was additionally noted that weakness was associated with functional disability and hospitalizations that occurred in the period before the study [ 28 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“… 5 ) While Fried Frailty predominantly assesses physical frailty, it also has good validity for assessing frailty. 5 , 28 , 29 ) We found that the Fried score was more closely related to physical parameters, while the TFI score was more associated with both psychosocial and physical parameters. Thus, the TFI is multidimensional and more comprehensive in evaluating frailty.…”
Section: Discussionmentioning
confidence: 65%
“…Frailty and functional status have been largely and consistently related to adverse health-related outcomes, and those results have been replicated in diverse scenarios of medical care. Frailty describes a predominantly biological syndrome, product of a diminished homeostatic reserve and poor resilience, which in turn increases the vulnerability of an individual, and correlates with a larger use of healthcare services, risk of immobility, disability, and death in diverse settings [10][11][12][13][14][15] . On the other hand, multi-comorbidity has been recently envisioned as an entity that correlates with synergistic poor health-related outcomes and complex management, rather than just a numerical descriptor of clinical conditions or an inventory of diseases 16 .…”
Section: Strategies For the Categorization Of Older Adults With Covid...mentioning
confidence: 99%